Intestinal and systemic inflammation induced by symptomatic and asymptomatic enterotoxigenic E. coli infection and impact on intestinal colonization and ETEC specific immune responses in an experimental human challenge model. (1st January 2021) - Brubaker, Jessica; Zhang, Xueyan; Bourgeois, A. Louis; Harro, Clayton; Sack, David A; Chakraborty, Subhra
ABSTRACT: Recent studies have gained a better appreciation of the potential impacts of enteric infections beyond symptomatic diarrhea. It is recognized that infections by several enteropathogens could be associated with growth deficits in children and intestinal and systemic inflammation may play an important underlying role. With enterotoxigenic E. coli (ETEC) being one of the leading causes of diarrhea among children in the developing world and important contributor to stunting, a better understanding of the impact of ETEC infection beyond diarrhea is timely and greatly needed. To address this, we evaluated if ETEC infection induces intestinal and systemic inflammation and its impact on colonization and immune responses to ETEC vaccine-specific antigens in a dose descending experimental human challenge model using ETEC strain H10407. This study demonstrates that the concentrations of myeloperoxidase (MPO) in stool and intestinal fatty acid-binding protein (an indicator of compromised intestinal epithelial integrity) in serum, significantly increased following ETEC infection in both diarrhea and asymptomatic cases and the magnitudes and kinetics of MPO are dose and clinical outcome dependent. Cytokines IL-17A and IFN-γ were significantly increased in serum post-ETEC challenge. In addition, higher pre-challenge concentrations of cytokines IL-10 and GM-CSF were associated with protection from ETEC diarrhea. Interestingly, higher MPO concentrations were associated with higher intestinal colonization of ETEC and lower seroconversions of colonization factor I antigen, but the reverse was noted for seroconversions to heat-labile toxin B-subunit. Together this study has important implications for understanding the acute and long-term negative health outcomes associated with ETEC infection.